International relations and the universality of human rights as a background for Islam's predicament with the Western concept of human rights - Ṭībī, Bassām (Islam and Christian-Muslim relations, 1992)
The author argues that individual human rights are an originally Western concept which has become universal. The concept of human dignity which exists in Islam must not be confused with that of human rights, as secular entitlements, which are lacking in Islam. Human rights are a common concern for all humanity. In admitting that the origin of the concept of human rights is Western, this author — who is a Muslim — emphasizes the universality of human rights and questions cultural relativism. However, he does not argue for an imposition of these rights on non‐Western cultures. There is a basic need for establishing cross‐cultural foundations of human rights. Without these, human rights cannot thrive in cultures in which they did not grow.